2023
DOI: 10.3389/frvir.2023.1108060
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a virtual reality based intervention on processing speed and working memory in individuals with ADHD—A pilot-study

Abstract: Introduction: This study aimed to evaluate the effectiveness of a virtual reality based intervention in processing speed and working memory in students with ADHD symptomatology.Methods: A randomized experimental study was conducted, with a sample consisting of 25 adult participants recruited from the Escola Superior de Saúde do Politécnico do Porto. The participants were allocated into two groups: a passive control group and an intervention group that completed 10 sessions using virtual reality-based games fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 78 publications
(99 reference statements)
0
9
0
Order By: Relevance
“…To determine the necessary sample size for evaluating the study hypothesis through mixed between-within subject design, an a priori power analysis was conducted using Gpower 3.1 software. The analysis was based on similar research (Cunha et al, 2023) and aimed to achieve an 80% power for detecting a medium effect size ( partial η 2 = .06), with a significance criterion of α = .05. The results indicate that a minimum sample size of N = 134 participants is required to achieve the desired statistical power.…”
Section: Methods and Analysismentioning
confidence: 99%
“…To determine the necessary sample size for evaluating the study hypothesis through mixed between-within subject design, an a priori power analysis was conducted using Gpower 3.1 software. The analysis was based on similar research (Cunha et al, 2023) and aimed to achieve an 80% power for detecting a medium effect size ( partial η 2 = .06), with a significance criterion of α = .05. The results indicate that a minimum sample size of N = 134 participants is required to achieve the desired statistical power.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Studies also showed that participants could better exhibit flexible and selfregulated behaviors [78,86,88]. Their thinking abilities were also more flexible [85,89]. It is notable that positive feelings increased, resulting in an increased motivation to continue practice [78,86,87,90,91].…”
Section: Vrgs For Meta-skills Training In Attention-deficit/hyperacti...mentioning
confidence: 99%
“…VRGs have a positive impact on mental operations that assure speed and flexible thinking [89]. A randomized experimental study evaluated the efficacy of VRGs on basic indicators for flexible and self-regulated thinking; namely, processing speed and working memory.…”
Section: Vrgs For Meta-skills Training In Attention-deficit/hyperacti...mentioning
confidence: 99%
“…Following a study of all 18 research papers, we discovered that 5 of them, accounting for a proportion of 27.7%, dealt with the topic of how attention training affects working memory. Overall, 4 out of 5 publications (80%) indicated improved working memory following attention training [11][12][13][14][15]. The most common form of technology was computer-based programs (60%, 3/5), wherein healthy younger and older adults were trained using a computerized mobile training application [12], children with autism spectrum disorder were trained using a computerized attention training program [13], and students in a primary school were trained using a computer-based training program [14].…”
Section: Rq1: What Types Of Technology-based Attention Training Have ...mentioning
confidence: 99%
“…The study proposed in [15] featured VR-based intervention. The VR games used were Whack-a-mole and Shuffled for attention, Memory Wall and Maestro for working memory, and Assembly and React for processing speed and task-switching/response inhibition skills.…”
Section: Rq1: What Types Of Technology-based Attention Training Have ...mentioning
confidence: 99%